Efektifitas Pembelajaran Jarak Jauh Terhadap Kepuasan Proses Pembelajaran Di Prodi D3 Dan S1 Akuntansi Untidar - Ayunda Putri Nilasari; Retnosari Retnosari; Supanji Setyawan (LP2M, 2021)
The purpose of this study is to analyze how distance learning can be used to achieve student satisfaction and to analyze that the implementation of distance learning is currently effective in achieving the objectives of the teaching and learning process during the current pandemic. The population of the study was all D3 and S1 students of Accounting, Faculty of Economics, Tidar University. The samples in this study were D3 and S1 Accounting students in semesters 1, 3 and 5 who were running their lectures. This study uses a combination of qualitative and quantitative research. The data collection technique used is in the form of a questionnaire using questionnaire that given to students to get an overview of the implementation of distance learning so far. In this quantitative analysis, the research variables are arranged descriptively by assessing the percentage of standard achievement in tabular form. The results of the implementation of distance learning by lecturers already had a variation or variety and the telegram learning media was the most widely used in the percentage of 87.6%. The ease of applying today's technology that makes learning media easily accessible to students is in the percentage of 55.9%. The level of student understanding of learning materials, information and deepening of material by 52.4% is currently effective in achieving the objectives of the Accounting teaching and learning process during the pandemic when it is 39%. Student satisfaction with distance learning that has been carried out during the pandemic is 40.2%.